Microstructure and properties of Ni-based alloy coatings on steel surface by sintering cladding - LI Xin-xing; WANG Hong-xia; SHI Jian-feng; HAN Yu-yang; JIANG Qiu-tong; LIU Yuan (Fenmo yejin jishu)
Ni-based alloy coatings on the 45 steel surface were prepared by sintering cladding method, using Ni25, Ni45, and Ni60 alloy powders, respectively. The microstructure, phase composition, and interface structure of the alloy coatings were analyzed by metallographic microscope and X-ray diffractometer, and the microhardness of the coatings was tested. The results show that, the relatively compacted Ni-based alloy coatings on the 45 steel surface can be obtained by sintering cladding technology. Ni25 alloy coatings are mainly consisted of the coarse γ-(Ni, Fe) austenite and a small amount of Cr23C6 carbide phase. In addition to the γ-(Ni, Fe) austenite and Cr23C6 carbide phases, the CrB boride phases also appear in the Ni45 and Ni60 alloy coatings. All of the three Ni-based alloy coatings have the good metallurgical bonding with the 45 steel matrix. The coatings show the dense microstructure with the fine particles uniformly distributed in the matrix, when the sintering temperature is 1100 ℃ and the holding time is 15 min. The Ni60 alloy coatings have the highest hardness, about HV 735; that of the Ni45 alloy coatings are the next, about HV 534; and the Ni25 alloy coatings show the lowest hardness, only HV 236.